STUDI KASUS PERILAKU KONSUMEN DALAM PEMBELIAN PRODUK DAGING AYAM POTONG DI “PRIMA FRESHMART” DESA SETIA MEKAR, KABUPATEN BEKASI - Budiyono, Haris; Rahmanto, M. Ikhwan; Riyan Hartono, Fawaz; Ardisela, Dawud (Fakultas Pertanian Universitas Islam 45 (UNISMA) Bekasi, 2023)
“Prima Freshmart” is a specialty store whose job is to offer several products for kitchen needs, such as chicken meat, eggs, frozen food, and other food and beverages at affordable prices. This research is to find out: (1) The influence of service variable has an effect on the decision to buy beef chicken at